Synthesis, antitumour activities and molecular docking of thiocarboxylic acid ester-based NSAID scaffolds: COX-2 inhibition and mechanistic studies - El-Azab, Adel S. (J Enzyme Inhib Med Chem, 2018)
A new series of NSAID thioesters were synthesized and evaluated for their in vitro antitumor effects against a panel of four human tumor cell lines, namely: HepG2, MCF-7, HCT-116 and Caco-2, using the MTT assay. Compared to the reference drugs 5-FU, afatinib and celecoxib, compounds 2b, 3b, 6a, 7a, 7b and 8a showed potent broad-spectrum antitumor activity against the selected tumour cell lines. Accordingly, these compounds were selected for mechanistic studies about COX inhibition and kinase assays. In vitro COX-1/COX-2 enzyme inhibition assay results indicated that compounds 2b, 3b, 6a, 7a, 7b, 8a and 8 b selectively inhibited the COX-2 enzyme (IC(50) = ∼0.20–0.69 μM), with SI values of (>72.5–250) compared with celecoxib (IC(50) = 0.16 μM, COX-2 SI: > 312.5); however, all the tested compounds did not inhibit the COX-1 enzyme (IC(50) > 50 μM). On the other hand, EGFR, HER2, HER4 and cSrc kinase inhibition assays were evaluated at a 10 μM concentration. The selected candidates displayed limited activities against the various tested kinases; the compounds 2a, 3b, 6a, 7a, 7b and 8a showed no activity to weak activity (% inhibition = ∼0–10%). The molecular docking study revealed the importance of the thioester moiety for the interaction of the drugs with the amino acids in the active sites of COX-2. The aforementioned results indicated that thioester based on NSAID scaffolds derivatives may serve as new antitumor compounds.